Organomineral fertilizers and soil remineralizer in the initial growth of mycorrhized Eucalyptus grandis W. Hill ex Maiden - Magalhães, Juliano Borela (2024)
The post-planting growth of eucalyptus requires proper fertilization to provide nutrients in adequate amounts for the seedlings. This study aimed to determine the contribution of organomineral fertilizers and soil remineralizers to the initial growth of mycorrhized Eucalyptus grandis. The experiment was conducted in a greenhouse at the Federal University of Santa Maria, Frederico Westphalen campus. The experimental design was completely randomized in a factorial arrangement (2x6), combined or not with inoculation of the ectomycorrhizal fungus Pisolithus microcarpus and six fertilizers (mineral fertilizer, mineral fertilizer with remineralizer, organomineral fertilizer, with two levels of phosphorus content — high and low), with five repetitions. After ninety days of cultivation, the height, stem diameter, number of leaves, dry mass of aerial parts, root dry mass, total dry mass, root volume, height/stem diameter ratio, Dickson Quality Index, relative growth efficiency index, and mycorrhizal colonization were evaluated. The results were submitted to analysis of variance and the means compared using Tukey’s test. The results showed that the organomineral fertilizer increased the morphological parameters and quality of Eucalyptus grandis, with the seedlings achieving greater mycorrhizal colonization in treatments with the remineralizer or organic fertilizer in the composition with the mineral fertilizer.